(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2018)
The power of digital distribution over physical retail outlets is you have a chance to create a global audience. This is exactly what the E-Commerce Industry is trying to capitalize, and they have been extremely successful in it. Name anything, and you get it at your doorstep with one click. Also, the E-Commerce industry has been aptly utilizing the consumer behaviour pattern, for example by providing discounts to expand their horizons. Has the introduction of GSTaffected the empire of E-Commerce?